THE EFFECT OF THE SHARIA SUPERVISORY BOARD AND THE BOARD OF COMMISSIONERS ON THE FINANCIAL PERFORMANCE OF SHARIA COMMERCIAL BANKS IN INDONESIA - Hasibuan, Ahmad Fauzul Hakim; Fuadi, Fuadi; Syahputra, Angga (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
This study aims to determine the influence of the Sharia Supervisory Board and the Board of Commissioners on the Financial Performance of Islamic Banks in Indonesia. This study used secondary data from 12 banks.The sampling technique used is the purposive sampling technique. The method of data analysis used is multiple linear regression.The results partially show that the sharia supervisory board and board of commissioners positively and significantly influence the financial performance of Islamic banks in Indonesia. Simultaneously,the board of commissioners and the sharia supervisory board positively and significantly influence the financial performance of Islamic bank